Electrochemical Corey–Winter reaction. Reduction of thiocarbonates in aqueous methanol media and application to the synthesis of a naturally occurring α-pyrone - López-López, Ernesto Emmanuel; Pérez-Bautista, José Alvano; Sartillo-Piscil, Fernando; Frontana-Uribe, Bernardo A. (Beilstein Journal of Organic Chemistry, 2018)
An electrochemical version of the Corey–Winter reaction was developed giving excellent results in aqueous methanol media (MeOH/H2O (80:20) with AcOH/AcONa buffer 0.5 M as supporting electrolyte), using a reticulated vitreous carbon as cathode in a divided cell. The electrochemical version is much more environmentally friendly than the classical reaction, where a large excess of trialkyl phosphite as reducing agent and high temperatures are required. Thus, cathodic reduction at room temperature of two cyclic thiocarbonates (−1.2 to −1.4 V vs Ag/AgCl) afforded the corresponding alkenes, trans-6-(pent-1-enyl)-α-pyrone and trans-6-(pent-1,4-dienyl)-α-pyrone, which are naturally occurring metabolites isolated from Trichoderma viride and Penicillium, in high chemical yield and with excellent stereo selectivity.
Keywords: Corey–Winter reaction; electrosynthesis; 6-pentyl-2H-pyran-2-ones; reduction; thiocarbonates